Understanding nurses' experiences with near‐miss error reporting omissions in large hospitals - Jaehee Lee (Wiley, 2021)
Abstract Aim This qualitative study aimed to provide an in‐depth understanding of nurses' experiences with near‐miss errors and report omissions known to be direct or indirect causes of medical accidents in hospitals and cited as precursors of serious medical accidents. Design This study collected experiences of research participants through an interview as a qualitative research method and confirmed the meaning through an inductive approach. Methods We selected nine nurses with various levels of experience from 27 May to 10 June 2019 for analysis. We adopted phenomenological research methods and procedures proposed by Colaizzi (Existential‐phenomenological alternative for psychology, 1978) and established the feasibility and integrity of our results based on narrative studies proposed by Lincoln and Guba (Naturalistic inquiry, 1985). Results This study demonstrated that near‐miss errors and report omissions experienced by professional nurses could be merged into the following themes: lack of cognitive susceptibility to near‐miss errors; confusion about the reporting system for near‐miss errors; lack of knowledge about near‐miss errors; disappointment with results of reporting near‐miss errors; and fear of reporting near‐miss errors. These results strongly suggest the need to improve recognition efforts based on a socio‐educational viewpoint involving the so‐called openness about failures.